2019
DOI: 10.31925/farmacia.2019.5.6
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antimicrobial Potential of New Azetidin-2-One of Ferulic Acid

MARIA DRĂGAN

Abstract: The objective of our study was to evaluate the antioxidant and antimicrobial potential for six new azetidin-2-one derivatives of ferulic acid. The in vitro antioxidant potential of the compounds was assessed by using the total antioxidant capacity and total reducing power assays. The antimicrobial activity was investigated using Gram positive bacteria (Staphylococcus aureus ATCC 25923), Gram negative bacteria (Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853) and pathogenic yeast (Candida albican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…Based on the results obtained on in vitro anti-inflammatory evaluation studies which were previously published [7,8] and from the literature data regarding the anti-inflammatory potential and mechanism of ferulic acid, our azetidin-2-one derivatives of ferulic acid were included in a pharmacological screening test aimed to determine the in vivo anti-inflammatory effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the results obtained on in vitro anti-inflammatory evaluation studies which were previously published [7,8] and from the literature data regarding the anti-inflammatory potential and mechanism of ferulic acid, our azetidin-2-one derivatives of ferulic acid were included in a pharmacological screening test aimed to determine the in vivo anti-inflammatory effect.…”
Section: Discussionmentioning
confidence: 99%
“…In those studies, the in vitro antioxidant potential of the azetidin-2-one derivatives of ferulic acid was assessed using the total antioxidant capacity, total reducing power assays, and DPPH and ABTS .+ radicals scavenging assays. The results showed that all the investigated compounds possess a good antioxidant activity at low concentrations, a more intense effect than ferulic acid and a comparable effect with ascorbic acid, used as positive control, was found for compound 6b (R = 4-F) [7,8]. Additionally, the in vitro anti-inflammatory potential was investigated using bovine serum albumin denaturation and human red blood cell membrane stabilization assays.…”
Section: Compound -R Compound -R 6amentioning
confidence: 96%
See 1 more Smart Citation
“…The reagent contains the following substances: sulphuric acid 0.6 M, sodium phosphate 28 mM and ammonium molybdate 4 mM. The absorbance of the sample was measured at 695 nm, using a blank which contains 2% acetic acid (50 µL) and the reagent solution (2 mL); effective concentrations (EC50) were calculated [24,25].…”
Section: Research Regarding Antioxidant Assaysmentioning
confidence: 99%
“…The absorbance of each sample was measured at 700 nm, using a blank that contains all reagents and less stock solution. The effective concentrations (EC50) were calculated for this method (also [24]).…”
Section: Research Regarding Antioxidant Assaysmentioning
confidence: 99%